Self-Perceived Readiness of Haitian Agricultural University Students to enter the Workforce: A Call for Curriculum Reform - Grady T. Roberts; Absalon Pierre; Anne C. Gilot; J. C. Bunch (Journal of International Agricultural and Extension Education, 2019)
The country of Haiti has faced chronic food insecurity for decades. Increasing domestic food production has been identified as a key part of the solution, but this requires building human capacity, especially related to agricultural extension and research. Haiti’s agricultural universities can be key players in this process. The purpose of this study was to explore the selfperceived readiness of Haitian agricultural university students to enter the workforce. Results revealed students had a wide variety of career aspirations and appreciated the breadth of the agronomy engineer degree. Students also expressed favorable opinions about their preparedness for the job market but felt pessimistic about finding a job. Students valued the importance of research and felt prepared to lead a research project. Finally, students thought all 17 Global Forum for Rural Advisory Services (GFRAS) New Extensionist competency areas were important. Recommendations for additional research and practice are provided.
Keywords: Haiti; agriculture; higher education; research; extension